2021
DOI: 10.1002/cyto.b.22048
|View full text |Cite
|
Sign up to set email alerts
|

The flow cytometry myeloid progenitor count: A reproducible parameter for diagnosis and prognosis of myelodysplastic syndromes

Abstract: Background: The bone marrow blast count is central to the diagnosis and monitoring of myelodysplastic syndromes (MDS). It is an independent risk factor for worse prognosis whether based on the morphology blast count or the flow cytometry (FC) myeloid progenitor (MyP) count. It is a principal population in FC MDS analysis also because once defined; it provides significant contributions to the overall FC MDS score. Methods:We elected to investigate inter-analyst agreement for the most fundamental parameter of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…Indeed, results of a survey by this group, which has led the path in implementing this test, show that a substantial number of institutions were using a suboptimal tube and acquiring an insufficient number of events (Tarfi et al, 2018), perhaps signaling that insufficient emphasis had been placed on specific details of the test, including the importance of the gating strategy. Our results indicating variable results when using different gating strategies—and thus highlighting the importance of the gating strategy when quantifying flow cytometric parameters—is in line with a recent illuminating study showing that different gating strategies led to substantially different results when quantifying CD34+ myeloid progenitors in the bone marrow (Johansson et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Indeed, results of a survey by this group, which has led the path in implementing this test, show that a substantial number of institutions were using a suboptimal tube and acquiring an insufficient number of events (Tarfi et al, 2018), perhaps signaling that insufficient emphasis had been placed on specific details of the test, including the importance of the gating strategy. Our results indicating variable results when using different gating strategies—and thus highlighting the importance of the gating strategy when quantifying flow cytometric parameters—is in line with a recent illuminating study showing that different gating strategies led to substantially different results when quantifying CD34+ myeloid progenitors in the bone marrow (Johansson et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…In CMML but not in other causes of monocytosis, intermediate and nonclassical monocytes are practically absent [Color figure can be viewed at wileyonlinelibrary.com] placed on specific details of the test, including the importance of the gating strategy. Our results indicating variable results when using different gating strategies-and thus highlighting the importance of the gating strategy when quantifying flow cytometric parameters-is in line with a recent illuminating study showing that different gating strategies led to substantially different results when quantifying CD34+ myeloid progenitors in the bone marrow(Johansson et al, 2021).…”
supporting
confidence: 86%
“…It has also identified an increased SSC of more mature erythroid cells as a highly informative feature of MDS-associated dysplasia (Duetz et al, 2021;Westers et al, 2023). This finding was independently confirmed by others using traditional analysis (Johansson et al, 2021). Likewise, Barreau et al (2020) developed a semi-automated approach for a MFC diagnosis of MDS.…”
Section: Computational Analysis/ Future Directionsmentioning
confidence: 73%
“…The value of the LSC frequency in AML is widely accepted for predicting survival and relapse at diagnosis and post-treatment, respectively [ 28 , 29 ]. In MDS, the myeloid progenitor count is used as a prognostic parameter in FCM scores, whereas we recently showed that manually gated LSCs predict leukaemic progression [ 20 , 23 , 30 ]. Yet, manual gating of the low-frequent LSCs is sensitive to errors.…”
Section: Discussionmentioning
confidence: 99%